Test–retest reliability of pivoting proprioception assessment and its association with physical activity in healthy young adults - Park, Kyung-Mi; Lee, Dawon; Lee, Jiyoon; Beom, Jaewon; Lee, Song Joo (대한의용생체공학회, 2026)
To (1) evaluate the test–retest (intra-rater) reliability of pivoting proprioception assessments and (2) investigate their association with physical activity levels in healthy young adults. Methods: Sixteen healthy individuals (8 male, 8 female) completed two testing sessions one week apart. Pivoting proprioception was assessed using angle matching and repositioning tests with a custom stepper system. Physical activity levels were assessed using the International Physical Activity Questionnaire (IPAQ) and the Tegner Activity Scale (TAS). Pivoting proprioceptive acuity was quantified as absolute error between target and reproduced angles. Test–retest reliability was analyzed using intraclass correlation coefficients (ICC), Bland and Altman plots with limits of agreement, standard error of measurement (SEM), and minimal detectable change (MDC). Associations between proprioceptive acuity and physical activity were examined using Pearson’s or Spearman’s rank correlation. Results: The repositioning test demonstrated almost perfect reliability (ICC = 0.81), while the angle matching test showed moderate reliability (ICC = 0.57). TAS scores were significantly negatively correlated with repositioning test errors (r = −0.53, p = 0.03), indicating better proprioceptive accuracy in more active individuals. IPAQ scores showed a negative correlation with repositioning test errors (r = −0.44, p = 0.09), but this was not statistically significant. Neither IPAQ nor TAS scores were significantly correlated with angle matching test performance (p > 0.05). Conclusion: Pivoting proprioception can be reliably assessed using the repositioning method, which demonstrates excellent test–retest reliability. Higher physical activity levels, particularly sport-related activities, are associated with superior proprioceptive accuracy in pivoting motion.